Specters of conquest : Indigenous absence in transatlantic literatures - Lifshey, Adam (Fordham University Press, 2010)
This book intervenes in transatlantic and hemispheric studies by positing 'America' not as a particular country or continent but a foundational narrative, in which conquerors arrive at a shore intent on overwriting local versions of humanity, culture, and landscape with inscriptions of their own design.